Astrovirus ribosomal frameshifting in an infection-transfection transient expression system. - Lewis, T L (1996)
Different regions of the human astrovirus frameshift signal were cloned into the rhesus rotavirus VP4 gene and evaluated in an infection-transfection transient expression cell culture system. BHK-21 cells, infected with a vaccinia virus that expresses T7 RNA polymerase (vTF7-3), were transfected with the various astrovirus-VP4 constructs. All constructs were driven by a T7 promoter and contained an internal ribosome entry site. Frameshifted and nonframeshifted protein products were immunoprecipitated with VP4 amino- and carboxy-terminal-specific monoclonal antibodies, and their ratios were determined by PhosphorImager analysis. The efficiency of frameshifting was 25 to 28%, significantly greater than the 5 to 7% efficiency reported previously in a cell-free translation system. Coupling of transcription and translation in a cell-free system yielded frameshifting efficiencies threefold greater than that of the uncoupled in vitro system. The presence of the shifty heptamer was an absolute requirement for frameshifting in both cell-free and intact-cell systems, while deletion of the potential downstream pseudoknot region did not affect the efficiency of frameshifting.